TRPC6 modulates adhesion of neutrophils to airway epithelial cells via NF-κB activation and ICAM-1 expression with ozone exposure - Chen, Qing-Zi; Zhou, Yu-Bo; Zhou, Li-Fen; Fu, Zhao-Di; Wu, You-Sen; Chen, Yan; Li, Shu-Ni; Huang, Jian-Rong; Li, Jian-Hua (Experimental cell research, 2019)
Ozone (O3) is a major component of air pollution, which has been associated with airway inflammation characterized by the influx of neutrophils in asthmatic subjects. Canonical transient receptor potential 6 (TRPC6) channel is recently identified as a target of oxidative stress which is involved in airway inflammation. However, the regulatory role of TRPC6 in airway epithelial cells and neutrophils has not yet been illuminated in detail. In this study, we investigated the role of TRPC6 in neutrophil adhesion to airway epithelial cells exposed to O3 in vivo and in vitro approaches. Using transgenic mice, the results showed that TRPC6-deficiency attenuated O3-induced neutrophil recruitment to airway epithelial cells and intercellular adhesion molecule-1 (ICAM-1) expression. In vitro, O3 induced ICAM-1 expression and neutrophil adhesion to 16HBE cells (human airway epithelial cell line) and which were reduced by both TRPC6 silencing short hairpin RNA (shRNA) and TRPC6 inhibitor Larixyl Acetate (LA). We also confirmed that TRPC6-dependent Ca2+ entry and NF-κB activation in 16HBE cells were required for ICAM-1-mediated neutrophil adhesion exposed to O3. In conclusion, this study demonstrated the contribution of TRPC6 to O3-induced neutrophil adhesion to airway epithelial cells via NF-κB activation and ICAM-1 expression, which may provide new potential concepts for preventing and treating air pollutant-related inflammatory lung diseases. •TRPC6-deficiency attenuated O3-induced neutrophil recruitment to airway epithelial cells and ICAM-1 expressions in vivo.•TRPC6 shRNA and TRPC6 inhibitor reduced O3-induced neutrophil adhesion to 16HBE cells and ICAM-1 expressions in vitro.•TRPC6-dependent Ca2+ influx regulated ICAM-1 expressions and neutrophil adhesion to airway epithelial cells exposed to O3.•NF-κB activation was involved in TRPC6-mediated neutrophil adhesion to airway epithelial cells exposed to O3.